2016
DOI: 10.1371/journal.pone.0157995
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical Factors Associated with Retinal Morphological Changes in Patients with Primary Sjögren's Syndrome

Abstract: PurposeTo investigate clinical factors associated with abnormal retinal morphologies in patients with primary Sjögren's syndrome (pSS).MethodsOne-hundred-thirty patients with pSS who underwent immunoserological tests, minor salivary gland biopsies, and optical coherence tomography examinations were retrospectively analyzed. Risk factors for abnormally reduced peripapillary retinal nerve fiber layer (pRNFL) and macular ganglion cell–inner plexiform layer (mGCIPL) thicknesses were evaluated, as well as the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The results of the multiple regression analysis showed that visual impairment was associated with retinal thinning. This is in agreement with previous studies demonstrating that the ganglion cell inner plexiform and retinal nerve fiber layers were thinner in patients with SS compared with healthy subjects ( 37 , 38 ). In healthy subjects, the inner RT is negatively correlated with age ( 39 ), which may be due to the loss of neurons, while the outer RT (especially RPE) may thicken with age ( 40 ).…”
Section: Discussionsupporting
confidence: 93%
“…The results of the multiple regression analysis showed that visual impairment was associated with retinal thinning. This is in agreement with previous studies demonstrating that the ganglion cell inner plexiform and retinal nerve fiber layers were thinner in patients with SS compared with healthy subjects ( 37 , 38 ). In healthy subjects, the inner RT is negatively correlated with age ( 39 ), which may be due to the loss of neurons, while the outer RT (especially RPE) may thicken with age ( 40 ).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies evaluated subclinical retinal changes in other autoimmune systemic disorders using SD-OCT. A study in patients with rheumatoid arthritis revealed no significant changes in pRNFL or total foveal thickness compared to healthy controls [35]. On the other hand, patients with primary Sjogren's syndrome present a significant reduction in pRNFL as well as in macular GCL compared to healthy controls [36]. Patients with Behçet's disease also present significant thinning in the pRNFL [37].…”
Section: Table 1 Demographic and Clinical Characteristics Of The Patients By Groupmentioning
confidence: 99%
“…Specifically, a reduced thickness of the peripapillary retinal nerve fiber layer and of the macular ganglion cell-inner plexiform layer, measured by OCT, have been reported in association with SS-B positivity and with elevated erythrocyte sedimentation rate (ESR) in SS patients (Fig. 2B) [111,112].…”
Section: Retinal Alterations In Sjögren's Syndromementioning
confidence: 97%
“…Particularly, the pathomechanism of retinal ganglion cells (RGCs) involvement might be based on the binding of the autoantibodies to apoptotic RGCs, which impairs the clearance of these cells by eliciting proinflammatory responses as macrophage infiltration and increased production of IL-1, TNFα, ET-1 and NO (Fig. 2B) [112]. This interesting hypothesis is also supported by a recent study exploring the autoimmune aspects of eye glaucomatous changes, which have detected accumulation of type G immunoglobulins (IgG) and increased levels of proinflammatory cytokines in the human glaucomatous retina (Fig.…”
Section: Retinal Alterations In Sjögren's Syndromementioning
confidence: 99%